EPIDEMIOLOGIC ASPECTS OF TRAUMA IN AL-JOUF REGION, SAUDI ARABIA: A RETROSPECTIVE STUDY - DOAA M ABDEL-SALAM; RAWAN R ALRUWAILI; FARAH S ALHABLANI; NOUR H ALFAHEL; F ALMUNAHI, AMAL; ANWAR A ALBLAWI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: This study aimed to determine the types, characteristics, and associated factors of trauma in Al-Jouf Region which is located in Northern part of Saudi Arabia. Methods: The present study was conducted in the Emergency Department of Prince Meteb Hospital in Al-Jouf Region. A total number of 382 patients were enrolled in the present study. A pre-organized data form were designed for each patient attended the Emergency Department of Prince Meteb Hospital from January 2017 to January 2018. It included data about sociodemographic characteristics, type of trauma, and trauma characteristics. Results: The mean age of the patients was 24.4±13.4 years. Most of the patients (75%) were <30 years old. Males (86.9%) were influenced by trauma more common than females. Most of the patients (84.8%) were from urban areas. Blunt trauma constituted 58.9% while, penetrating trauma 41.1%. The most common cause of trauma was road traffic accidents, which occurred among 40% of patients. The most frequent trauma site was head trauma (49%). Most of the patients (47.9%) reached the hospital within 30 min. Regarding the fate of patients, 46.1% discharged after management, 42.1% admitted to intensive care units, and only 11.8% died. Blunt trauma was significantly higher than penetrating trauma among the young age group. Patients with blunt trauma arrived hospital significantly earlier than patients with penetrating trauma. The fate of patients is significantly better in blunt trauma than penetrating trauma. Conclusion: Trauma is considered to be a major public health problem, particularly in the young population in Saudi Arabia. Blunt trauma is more common than penetrating trauma, with road traffic accidents representing the majority.